EFEKTIVITAS DAN DAMPAK BANTUAN SOSIAL TERHADAP KESEJAHTERAAN MASYARAKAT PENERIMA KUBE DI KABUPATEN BADUNG - Eva Yuliantari, Ni Luh; Aswitari, Luh Putu (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2018)
Welfare is a feasibility level of community life that is viewed from the economic and social side. Many government programs aimed at improving welfare, especially the welfare of the poor, one of which is social assistance in the form of empowerment of Joint Business Group (KUBE). The purpose of this study is to analyze the effectiveness and impact of social assistance on the welfare of the recipient community of KUBE in Badung regency. This study uses primary data obtained from interviews and observations and secondary data obtained from the Central Bureau of Statistics (BPS) of Badung and Bali Province as well as data from the Social Service and Labor of Badung Regency. This research was conducted in three sub-districts in Badung regency namely Petang Subdistrict, Abiansemal Subdistrict and Mengwi Sub-District. This study uses a quantitative approach in the form of a comparative. Data analysis technique in this research is using different test with wilcoxon method. The results of this study are as follows: 1) the effectiveness of social assistance for the welfare of the people in Badung Regency is quite effective, 2) social assistance has no significant impact on the welfare of society in Badung regency. Keywords : Welfare, poverty, social assistance, KUBE, effectiveness